Ice age: Collision course Collision course - Thurmeier, Mike; Romano, Ray; Leary, Denis; Leguizamo, John; Beatriz, Stephanie; Twentieth Century Fox Home Entertainment, Inc. (2016)
Scrat's epic pursuit of the elusive acorn catapults him into the universe where he accidentally sets off a series of cosmic events that transform and threaten the Ice Age World. To save themselves, Sid, Manny, Diego, and the rest of the herd must leave their home and embark on a quest full of comedy and adventure, traveling to exotic new lands and encountering a host of colorful new characters.
Wide screen.
Bonus features: Ice age: collision course in high definition; Scrat: spaced out mini-movie; Ice age: the story so far; Scratasia: Scrat's solo adventures; Mysteries of the Scratazons; The science of it all: DeGrasse Tyson debunks; Star signs of the animal kingdom; "Figaro" sing-along; gallery.
Ray Romano, Denis Leary, John Leguizamo, Stephanie Beatriz, Robert Cardone, Neil Degrasse Tyson, Adam Devine, Jesse Tyler Ferguson, Max Greenfield, Queen Latifah.
MPAA rating: PG; for mild rude humor and some action/peril CHV rating G.
DVD.
English, Spanish or French dialogue; Spanish or French subtitles; subtitled for the deaf and hard of hearing (SDH); described video; Closed-captioned.
Keywords: Glacial epoch -- Juvenile films; Asteroids -- Juvenile films; Crystals -- Juvenile films; Mammoths -- Juvenile films; Feature films; Children's films; Animated films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities